Policy Framework of Green Taxation on Motor Vehicles: A Comparative Perspective - Singh, Kanwal DP; Gahlot, Sheetal (European Journal of Sustainable Development, 2023)
Green economics is structured to reward more innovative, environmentally sustainable, and low-carbon resource use while imposing taxes on the emission of pollutants that adversely impact the environment and public health. The concept of green taxation is still being tested in many nation-states. Pollution is worst in India, and the country is ranking low on several environmental performance indices. Vehicle exhausts are one of the key pollutants. In 2021, the Indian government released draft guidelines for imposing Green Tax on older motor vehicles. India submitted its first Nationally Determined Contribution Report to the United Nations Framework Convention on Climate Change in 2022. India prioritized green taxonomies, low-carbon transportation systems, and Bharat Stage-VI emission standards and offered incentives and tax breaks to encourage the production and use of higher ethanol-compatible vehicles. There is still a lack of awareness among the masses, as well as academic discussions and literature on the subject. Against this backdrop, the researchers intend to explore the legal and economic actions undertaken by the Indian Government to intercept vehicular air pollution. An effort will also be made to draw a comparative study with the fiscal policy measures and other steps taken by the Italian government to tax polluting vehicles. Keywords: Green Taxation, Vehicular Pollution, Economic Incentives, Environmental Protection, Sustainable Development